Emancipation's Daughters : Reimagining Black Femininity and the National Body - Richardson, Riche, 1971- (Book collections on Project MUSE., 2021)
"Emancipation's Daughters examines black women political leaders who have challenged oppressive models of black womanhood since Emancipation, including slavery's assault on the black maternal body reflected in the Aunt Jemima stereotype. In spite of the abjection associated with black womanhood within the slave system of the antebellum era, Sojourner Truth and Harriet Tubman defied it, established prominent public voices, and emerged as leaders and national emblems through their contributions to the struggle for freedom. They established foundations for the emergence of black women political leaders throughout the twentieth century and into the new millennium who have challenged this oppressive script. In the process, they unsettle models of U.S. identity premised on whiteness that have framed white women as the only acceptable national symbols within the conventional patriarchal scripts of national selfhood, and resist the devaluation of black womanhood on the basis of race, class, gender and sexuality"--